Ecolodges and tourism development: Planning and design contradictions and the consequences for historically disadvantaged communities in South Africa - Anyumba, Godfrey (Acta Structilia, 2009)
Contradictions exist between the theoretical ecolodge as the idyllic rustic shelter set amid a variety of ecotourism destinations and its actual realization as a tourism-architectural object. This article briefly illustrates the discrepancy between the theoretical ’ideal’ ecolodge and ecolodges in general. The former or ideal ecolodge is an adoption of the traditional buildings of the communities at the tourist destinations. The latter is often an eclectic comodification of the indigenous artefacts by architects for developments by large investment corporations. This article hypothesizes that the repercussions of ’ecolodge contradictions’ are readily recognizable in the instances when Historically Disadvantaged Communities (HDC) wish to partake in the tourism industry. The irony is that the indigenous people whose architecture, art forms and other cultural symbols are commercially immitated, are not in the position to enter the mainstream of the South African tourism industry because of the high inset costs.